When free markets fail :saving the market when it can't save itself / Scott McCleskey - McCleskey, Scott.
Authoritative guidance for navigating inevitable financial market regulation The reform of this country s financial regulation will be one of the most significant legislative programs in a generation. When Free Markets Fail outlines everything you need to know to stay abreast of these changes. Written by Scott McCleskey, a managing editor at Complinet, the leading provider of risk and compliance solutions for the